Supporting Students' Scientific Literacy Skills Through an Experimental KIT Module Based On Al-Quran Studies - Ahmad Zohdi; Azmar Azmar (Postgraduate, University of Mataram, 2023)
The transition from industry 4.0 to 5.0, the transformation of education into a worldwide challenge that emphasizes students' scientific literacy abilities in preparation for the future workforce. To promote scientific literacy, learning resources that support student abilities are required. In constructing an experimental physics KIT based on Al-Qur'an studies with the primary goal of enhancing students' scientific literacy, integrating students' spiritual values and scientific understanding is, thus, a central concern. The research design employed was the 4D Model (Definition, Design, Development, and Deployment), with a sample of Tadris Physics students enrolled in the fifth semester at UIN Mataram. Validity analysis, usability analysis, and effectiveness analysis are the techniques utilized for analysis. During the assessment, 83.33 percent of students demonstrated mastery of classical skills, classified as highly proficient. As a form of mastery learning, the test results indicate that developing experimental KIT modules based on Al-Qur'an studies is highly beneficial in supporting students' scientific literacy skills. In addition, the module development learning materials can promote the achievement of psychomotor, cognitive, and spiritual outcomes for students